Iron Catalyst and Blue Light Partnership for Selective Desulfurization of Secondary and Primary Thioamides - Zhang, Qingxin; Berro, Mahdi; Darcel, Christophe (Synthesis, 2025)
Commercially available iron(0) Fe2(CO)9 precatalyst can promote the selective desulfurization of secondary and primary carboxamides leading to the corresponding secondary amines and nitriles, respectively. The reaction is conducted under hydrosilylation conditions using phenylsilane or diethylsilane and blue LED irradiation (2 × 24 W, 450–460 nm) at ambient conditions.
Keywords: Iron catalysis; Desulfurization; Hydrosilylation; Secondary thioamide; Primary thioamide; Blue light